Предмет: Математика, автор: andreyyy30

Решите пожалуйста
Срочно

Приложения:

Ответы

Автор ответа: Eliz111111222
0
( frac{2y}{x} - frac{x}{2y} ) div (2y + x) = (frac{4 {y}^{2} }{2yx} - frac{ {x}^{2} }{2yx} ) div (2y + x) = frac{4 {y}^{2} - {x}^{2} }{2yx} div (2y + x) = frac{4 {y}^{2} - {x}^{2} }{2yx} times frac{1}{2y + x} = frac{(2y - x)(2y + x)}{2yx} times frac{1}{2y + x} = frac{2y - x}{2yx}
Автор ответа: andreyyy30
0
Это что за херня
Автор ответа: andreyyy30
0
??
Похожие вопросы
Предмет: Алгебра, автор: лев70